Задача о дифракции нестационарной плоской поперечной волны на сферическом включении в упруго-пористом пространстве (SCIENCE and SOCIETY, 2022)
The paper considers the problem of diffraction of non-stationary transverse shear waves on a spherical inclusion in a porous-elastic space saturated with liquid. Numerical experiments were carried out, the results of which are presented in the form of graphs.